The Power Mean Test - Kulhanek, Travis E; Ponomarenko, Vadim (The PUMP Journal of Undergraduate Research, 2020)
We devise a new test for convergence or divergence of an infinite series — the Power Mean Test. We explore the strength of this test relative to that of the Ratio and Root Tests and provide a family of series where the Power Mean Test is the most useful of the three tests.